Autoimmune and inflammatory diseases associated with chronic myelomonocytic leukemia: A series of 26 cases and literature review. (August 2016) - Grignano, Eric; Mekinian, Arsene; Braun, Thorsten; Liozon, Eric; Hamidou, Mohamed; Decaux, Olivier; Puéchal, Xavier; Kahn, Jean Emmanuel; Schoindre, Yoland; Rossignol, Julien; Lortholary, Olivier; Lioger, Bertrand; et al.
Highlights: Vasculitis are the most frequent autoimmune diseases associated with CMML. CMML features are worse when associated to SAIDs. Hypomethylating agents may represent an alternative therapy after steroids. Abstract: We wanted to describe the characteristics, treatment and outcome of autoimmune and inflammatory diseases (SAIDs) associated with chronic myelomonocytic leukemia (CMML), and conducted a French multicenter retrospective study and a literature review. We included 26 cases of CMML (median age 75 years, 54% female), 80% with CMML-1. CPSS score was low (0 or 1) in 75% of cases. SAIDS was systemic vasculitis in 54%. Diagnosis of the 2 diseases was concomitant in 31% cases, and CMML was diagnosed before SAIDs in 12 cases (46%). First line treatment for SAIDs consisted mostly of steroid, with 85% of response. Second-line treatment was needed in 40% cases. Six patients received hypomethylating agents, with 66% response on SAIDs. A literature review found 49 cases of CMML-associated SAIDs, in whom SAIDs was systemic vasculitis in 29% cases. Hence, vasculitis is the most frequent SAIDs associated with CMML. After initial response to steroids, recurrence and steroid-dependence were frequent. Hypomethylating agents may be interesting in this context.